Mengaktifkan Belajar Siswa melalui Kartu Bilangan Bersama Kartu Huruf pada Mata Pelajaran Matematika dan Bahasa Indonesia di Sekolah Dasar - Ganjar Winata (Balitbangda Provinsi Lampung, 2018)
Activating Students Learning Through Numeral Card With Letter Card in Math and Indonesian Language Lessons in Elementary School. Teacher who teach classically will not fulfill her aim, until the students become passive. If this is happened continuously, it will ensue fatally. The students interest toward lesson will decrease so that the score will become lower. Those problem should be handled with teaching method which using media, in the case of the writer used numeral card and letter card as a media. It can be hoped with those media, the students activity will increase so that learning aim can be reached. The research has done with the research object are students in Ia grade SDN 2 Kelapa Tujuh Kecamatan Kotabumi Selatan Lampung Utara that amounted 30 students. The lesson which will research is Math and Indonesian Language lessons. As we can see in finding data and reflection, activity in learning is increased. The students become more aggressive toward lesson which is delivered by teachers. Learning process become more alive and meaningful. The lesson comprehension process will become faster because the students attract to understand the lesson. The students who did not want to ask become little extrovert and brave to ask. It can be seen from the increasing of score percentage in Math and Indonesian Language lesson. The increasing of score indirectly caused by the applying of media in learning process of both lessons.